SpongeBob SquarePants. Karate island - Kenny, Tom (Thomas J.); Bumpass, Rodger; Fagerbakke, Bill, 1957-; Lawrence, Carolyn; Brown, Clancy; Blue Hawaiians; Paramount Pictures Corporation (Hollywood, Calif. : Paramount Pictures, 2006)
Dwelling on the tropical isle of Bikini Atoll, under the sea in the city of Bikini Bottom, SpongeBob lives in a two -story pineapple. Instead of taking the logical approach to everyday challenges, SpongeBob approaches life in a wayward and unconventional way. Whether searching for the ultimate spatula to perfect his burger flipping technique at the Krusty Krab, or just hanging out with his best friend Patrick, SpongeBob's good intentions and overzealous approach to life usually create chaos in his underwater world.
SquidBob TentaclePants -- Krusty Towers -- Mrs. Puff, you're fired -- Ghost host -- Wishing you well -- Karate Island -- New leaf.
Title from container.
Based on the characters created by Stephen Hillenburg.
"Nick"--Container.
Editor, Lynn Hobson ; music, The Blue Hawaiians ; animation directors, Sean Dempsey, Edgar Larrazabal, Fred Miller, Andrew Overtoom, Frank Weiss, Tom Yasumi.
Voices: Tom Kenny, Rodger Bumpass, Bill Fagerbakke, Carolyn Lawrence, Clancy Brown.
Not rated.
Keywords: SpongeBob SquarePants (Fictitious character) -- Drama; Marine animals -- Drama; Friendship -- Drama; Television programs; Animated television programs; Television programs for children; Television comedies; Video recordings for the hearing impaired; Children's -- Animation -- Television series; Comedy -- Animation -- Television series; Animated television programs; Children's television programs; Comedy television programs